The association of cultural orientation with adherence to social distancing behaviors during the early COVID-19 pandemic in the United States: A cross-sectional survey - Rachel Dinero; Allison Pieczonka; Brittany L. Kmush (PLOS Global Public Health, 2022)
Non-pharmaceutical interventions are one of the major tools to prevent the spread of SARS-CoV-2. Information about these behaviors is disseminated by messaging campaigns. However, people differ in their responses to persuasive messages. Here, we examine whether cultural orientation is associated with adherence to recommended COVID-19 prevention guidelines. Participants (n = 443, 201 from the United States via Amazon Mechanical Turk and 242 from Central New York via a convenience, snowball sample) completed an online survey during April and May 2020. Cultural orientation was measured via the Horizontal and Vertical Individualism and Collectivism Scale. Adherence to limiting social contact was self-reported. Multi-level Poisson regression assessed the association between cultural orientation and social contact behaviors. Those high in horizontal individualist characteristics had a positive association with increased social contact behaviors (RR: 2.20, 95%CI: 1.97–2.47, p<0.001). Those high in vertical collectivist characteristics had a negative association with those behaviors (RR: 0.59, 95%CI: 0.52–0.67, p<0.000). We found an association with cultural orientation and adherence to social contact behaviors during the beginning of the COVID-19 pandemic. In the United States, effective public health messages to promote adherence to preventative behaviors should be tailored to horizontal individualists, those least likely to engage in recommended behaviors.